Village, Power and Local Actors: Identifying the Motivations of Village Heads Candidates and the Responses of Local Actors (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2021)
This study analyzes the factors that motivate the candidates who run for Village Head in Air Hangat District, Kerinci Regency, Jambi Province. In determining the informants, the researcher used the purposive sampling technique, and the data was collected using interviews and documentation studies. Test the validity of the data using source poles. The results showed intrinsic and extrinsic motivations for the Village Head candidates in the 2019 Village Head Election (Pilkades) in Air Hangat District. Intrinsic motivation consists of motivation to gain achievement, power, income, and prestige. Extrinsic motivation consists of developing human resources and providing a sense of security, comfort, and harmony. Based on the study results, it showed that the quality of Village Head candidates in the 2019 Village Head Election (Pilkades) was still at a low level. It can be seen from the low level of education and work experience in government. Community leaders, traditional leaders, and religious leaders are also of the view that village head candidates do not have the readiness to become village heads with a lack of experience in leadership.